Examining the Relationship Between Schizotypy and Self-Reported Visual Imagery Vividness in Grapheme-Color Synaesthesia - Janik McErlean, Agnieszka B.; Banissy, Michael J. (Frontiers in Psychology, 2016)
Synaesthesia is a condition in which one property of a stimulus triggers a secondary experience not typically associated with the first (e.g. seeing achromatic graphemes can evoke the perception of colour). Recent work has explored a variety of cognitive and perceptual traits associated with synaesthesia. One example is in the domain of personality, where higher rates of positive schizotypy, agreeableness, and openness to experience have been reported in synaesthetes that experience colour as their evoked sensation relative to typical adult controls. Additionally, grapheme-colour synaesthetes have previously been reported to show elevated mental imagery compared to typical adults. Here, we aimed to further elucidate the relationship between personality, synaesthesia, and other cognitive traits. In Study 1, we examined self-reported schizotypy and self-reported visual imagery vividness in grapheme-colour synaesthetes and typical adults. Our results partially replicated previous findings by showing that synaesthesia was associated with greater positive schizotypy and enhanced self-reported imagery vividness. The results also extend previous reports by demonstrating that differences in positive schizotypy and mental imagery vividness are not related in grapheme-colour synaesthesia. In Study 2, we sought to build on prior work showing lower agreeableness and increased openness to experience in synaesthetes by examining whether grapheme-colour synaesthesia is associated with other conceptually related traits; namely lower self-monitoring and increased sensation seeking. We did not find any differences between synaesthetes and controls on either of these traits. These findings are discussed in relation to potential factors that may contribute to the observed personality profile in grapheme-colour synaesthesia.